(Re)inventando o autêntico: arte, política e mídia na trajetória intelectual de Ariano Suassuna - Bezerra, Amilcar Almeida (2014)
ABSTRACT In this work, we describe artistic and intellectual trajectory of Ariano Suassuna - writer and playwright from Paraiba settled for more than six decades in Recife - since his first plays, until the national consecration achieved with the recent release of his thought and work by major mass media in Brazil. Suassuna s trajectory is emblematic for comprehending the structure of a cultural field according to Pierre Bourdieu - in Pernambuco. On the other hand, Suassuna is one of the few authors from northeast to achieve national and international reputation that have never settled out of the region or even out of the country. Because of the adaptations of his plays and romances produced by Globo TV and his collaboration as a columnist for major print media, such as Folha de São Paulo, Suassuna end up turning into a national celebrity in the 1990s. Through the analysis of texts published by the author, especially in newspapers, we identify the affiliations of their main nationalist thought and its unconditional defense of the popular pre-modern cultures of the Northeast, as well as the movements of his intellectual trajectory in relation to artistic, political and media institutions of his time. Finally, we aim to understand the meanings of appropriation of romanticregionalist discourse by contemporary national media as a sign of authenticity